The life and crimes of hoodie rosen eaudiobook - Blum, Isaac (Listening Library, 2022)
LONGLISTED FOR THE NATIONAL BOOK AWARD! A WILLIAM C. MORRIS AWARD WINNER! The Chosen meets Adam Silvera in this irreverent and timely story of worlds colliding in friendship, betrayal, and the hatred that divides us. Hoodie Rosen's life isn't that bad. Sure, his entire Orthodox Jewish community has just picked up and moved to the quiet, mostly non-Jewish town of Tregaron, but Hoodie's world hasn't changed that much. He's got basketball to play, studies to avoid, and a supermarket full of delicious kosher snacks to eat. The people of Tregaron aren’t happy that so many Orthodox Jews are moving in at once, but that’s not Hoodie’s problem. That is, until he meets and falls for Anna-Marie Diaz-O’Leary—who happens to be the daughter of the obstinate mayor trying to keep Hoodie’s community out of the town. And things only get more complicated when Tregaron is struck by a series of antisemitic crimes that quickly escalate to deadly violence. As his community turns on him for siding with the enemy, Hoodie finds himself caught between his first love and the only world he’s ever known. Isaac Blum delivers a wry, witty debut novel about a deeply important and timely subject, in a story of hatred and betrayal—and the friendships we find in the most unexpected places. Praise for The Life and Crimes of Hoodie Rosen : “A deeply authentic story about the terror and glory of encountering the outside world without sacrificing who you are—and who you want to be. It’s touching, tragic, and as Jewish as your Bubbe’s cholent.” –Gavriel Savit, New York Times bestselling author of Anna and the Swallow Man “Blum gives the common but often-dismissed spiritual journey of many teens the respect it deserves in this witty, profound look at cross-cultural friendship, courageous honesty, and how a willingness to truly see and love our neighbors can change an entire community.” –Vesper Stamper, National Book Award-nominated author of What the Night Sings “A refreshingly human look at the day-to-day nuances of Orthodox Judaism and the terror of modern antisemitism. I laughed, I gasped, I craved kosher Starburst. Two thumbs up from this nice Jewish girl!” –Tyler Feder, Sydney Taylor Award-winning author of Dancing at the Pity Party “Bold, brave, and brutally honest, it holds a permanent piece of my heart.” –Dahlia Adler, author of Cool for the Summer "Isaac Blum has the rare talent of telling searing, visceral truths in a witty, funny, punchy way . . . The Life and Crimes of Hoodie Rosen is a vital voice in Jewish YA canon." –Katherine Locke, Sydney Taylor Honor author of The Girl with the Red Balloon